Calton Point or Catton Point? A Misprinted Toponym on the Yukon Coast - Burn, C.R. (ARCTIC, 2013)
Capt. John Franklin’s account of his journey along the western Arctic coast of North America presents two spellings of the toponym he gave to the point at the eastern end of Workboat Passage, the strait between Herschel Island and the mainland. “Pt. Catton” is printed in the text, and “Pt. Calton” on the accompanying map compiled by Lt. E.N. Kendall. One of these must be a misprint. Catton Point and Calton Point have been used by the National Topographic System and on Canadian hydrographic charts. Calton Point was adopted by the Government of Canada for use in November 1962. However, Catton Point is almost certainly the intended toponym after the Rev. Thomas Catton, FRS (c. 1758 – 1838), President of St. John’s College, Cambridge (1819 – 22), and tutor when John F.W. Herschel arrived at the college in 1809. Catton was one of 13 fellows of the Royal Society honoured by Franklin in northern Yukon. No Calton has ever been elected to the Royal Society or included in the Dictionary of National Biography. Dans le récit de son expédition tout au long de la côte ouest de l’Arctique de l’Amérique du Nord, le capitaine John Franklin a écrit de deux manières différentes le toponyme qu’il a donné à la pointe est du passage Workboat, soit le détroit entre l’île Herschel et la terre ferme. La graphie « Pt. Catton » est employée dans le texte, tandis que la graphie « Pt. Calton » est utilisée sur la carte d’accompagnement compilée par le lieutenant E.N. Kendall. L’une des deux graphies doit être une erreur. Au fil des ans, Catton Point et Calton Point ont été utilisés par le Système national de référence cartographique ainsi que sur des cartes hydrographiques du Canada. Le nom de Calton Point a été officiellement adopté par le gouvernement du Canada en novembre 1962. Cependant, il est presque certain que Catton Point était le toponyme désiré, d’après le nom du révérend Thomas Catton, MSR (v. 1758-1838), président du collège St. John’s à Cambridge (1819-1822) et tuteur lorsque John F.W. Herschel est arrivé au collège en 1809. ...